A practice-specificity-based model of arousal for achieving peak performance - Movahedi, A.; Sheikh, M.; Bagherzadeh, F.; Hemayattalab, R.; Ashayeri, H. (Journal of Motor Behavior, 2007)
The authors propose a practice-specificity-based model of arousal for achieving peak performance. The study included 37 healthy male physical education students whom they randomly assigned to a high-arousal (n = 19) or low-arousal group (n = 18). To manipulate participants' level of arousal, the authors used motivational techniques. They used heart rate and the Sport Competition Anxiety Test (R. Martens, 1977) to measure the level of arousal that participants achieved. At the determined and given arousal state, the 2 groups performed the task (basketball free throws) for 18 sessions. Both groups performed a retention test at the 2 arousal levels immediately after the last exercise session, in the posttest, and after 10 days. Results showed that both groups learned the task similarly and achieved their peak performance at their experienced arousal level. When tested at an arousal level that differed from the one that they experienced throughout practice sessions, participants' performance had deteriorated significantly. Performance of the task seemed to have integrated with the arousal level of the participants during the task learning. The findings of this study suggest a practice-specificity-based explanation for achieving peak performance.